2010
DOI: 10.1007/s12519-010-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic extensive colectomy with transanal Soave pull-through for intestinal neuronal dysplasia in 17 children

Abstract: Laparoscopic procedure for left colectomy and subtotal colectomy with transanal Soave pull-through in infants and children with IND is safe, feasible, and effective. The location of barium stagnation in proximal margin may be used as a method to predict initially the proximal margin of the resected bowel segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
2
15
0
1
Order By: Relevance
“…4,7,8 No patient in the present study developed anastomotic leakage. This compares favorably with the 10% to 15% of septic complications reported after low CRA for rectal cancer, 15 and with the 3% to 17% of anastomotic leak after total colectomy with ileorectal anastomosis.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…4,7,8 No patient in the present study developed anastomotic leakage. This compares favorably with the 10% to 15% of septic complications reported after low CRA for rectal cancer, 15 and with the 3% to 17% of anastomotic leak after total colectomy with ileorectal anastomosis.…”
Section: Discussionmentioning
confidence: 51%
“…Since this publication, 4 studies including a total of 32 patients have reported the results of the Deloyers procedure, and all have focused on Hirshsprung disease and severe chronic constipation. [5][6][7][8] Recently, a retrospective study of 3 patients also gave results of this right colonic transposition technique, performed for synchronous colorectal tumors and segmental colonic Crohn's disease. 10 In our series, the 2 main indications for the Deloyers procedure were Hartmann reversal and previous colorectal anastomosis-related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is not a wellestablished role to surgical treatment as in Hirshcprung's disease, there are some reports of this modality of treatment in INDB [83] . Surgical treatment can be performed through different techniques [11,46,63,92] . Schärli [11] (1992) reported favorable results with a posterior sphincteromyotomy in 13 patients, after a limited 6 mo followup period.…”
Section: Treatmentmentioning
confidence: 99%
“…The criteria described by MeierRuge et al [22] (2004) and slightly altered by MeierRouge et al [5] [5,77,92] . The results obtained with these different types of treatment are very discordant.…”
Section: Diagnosismentioning
confidence: 99%